Beilschmiedia jacobii sp. nov. (Lauraceae), from Agasthyamala Biosphere Reserve of southern Western Ghats, India - Robi, A.j.; Udayan, P.s.; George, Satheesh; Sujanapal, P. (Phytotaxa, 2016)
A new species of Beilschmiedia Nees (Lauraceae) from India, B. jacobii, is described and illustrated. Beilschmiedia jacobii is similar to B. wightii, but can be distinguished by its shrubby habit, prominently lenticellate bark, thickly coriaceous small leaves with 5–7 lateral veins, and pubescent terminal buds. Ecological aspects and the distribution of the new species are also provided.